2015
DOI: 10.1038/ismej.2015.127
|View full text |Cite
|
Sign up to set email alerts
|

Microorganisms linked to inflammatory bowel disease-associated dysbiosis differentially impact host physiology in gnotobiotic mice

Abstract: Studying host-microbiota interactions are fundamental to understanding the mechanisms involved in intestinal homeostasis and inflammation. In this work, we analyzed these interactions in mice that were mono-associated with six microorganisms that are representative of inflammatory bowel disease (IBD)-associated dysbiosis: the bacteria Bacteroides thetaiotaomicron, adhesive-invasive Escherichia coli (AIEC), Ruminococcus gnavus and Roseburia intestinalis; a yeast used as a probiotic drug, Saccharomyces boulardii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 77 publications
4
89
1
1
Order By: Relevance
“…Comparative analysis using the weighted UniFrac distance indicated that the difference between CD and non-IBD controls was more marked than that between UC and non-IBD controls. These observations are compatible with the results of previous studies of fecal samples [33,34]. A focal alteration of the microbial structure within the inflamed mucosa of IBD has been reported previously [35].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Comparative analysis using the weighted UniFrac distance indicated that the difference between CD and non-IBD controls was more marked than that between UC and non-IBD controls. These observations are compatible with the results of previous studies of fecal samples [33,34]. A focal alteration of the microbial structure within the inflamed mucosa of IBD has been reported previously [35].…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with those of previous reports of fecal samples [1,3,4]. The pathological role of the genus Escherichia has been shown in many studies of adhesive-invasive E. coli [3,4,33], and R. gnavus has been reported to contribute to the pathophysiology of IBD through its mucolytic activity [35]. The genera Faecalibacterium, Coprococcus and Roseburia are the main butyrate-producing bacteria belonging to the order Clostridiales [36,37], and play a beneficial role in maintaining gut health.…”
Section: Discussionsupporting
confidence: 91%
“…Ruminococcus exerts pro-inflammatory effects and contributes to inflammatory bowel disease (IBD) pathogenesis [28]. Ruminococcus transplantation in germ-free mice enhances interferon-γ, interleukin 17, and interleukin 22 amounts [29]. Dialister was shown to be associated with antepartum preeclampsia samples [30].…”
Section: Resultsmentioning
confidence: 99%
“…(7) Given the abovementioned disorders' association with dysregulation of the human microbiome, interest has mounted in the use of probiotics to treat both irritable bowel syndrome (IBS), and inflammatory bowel disease (IBD). While dysbiosis remains a likely, (12)(13)(14) but as yet poorly understood mechanism for IBD and IBS, this has not stunted the a priori assumption by many clinicians and patients that probiotics may be helpful.…”
Section: Introductionmentioning
confidence: 99%
“…While their etiologies are unknown, they are both likely related to a dysregulated interaction between the normal intestinal microbiota and the host immune system. (12,13) Probiotics have been difficult to study (3), largely because they defy typical drug classification in many settings:…”
mentioning
confidence: 99%